2021
DOI: 10.3390/ijms22147281
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Envelope Integrity in Health and Disease: Consequences on Genome Instability and Inflammation

Abstract: The dynamic nature of the nuclear envelope (NE) is often underestimated. The NE protects, regulates, and organizes the eukaryote genome and adapts to epigenetic changes and to its environment. The NE morphology is characterized by a wide range of diversity and abnormality such as invagination and blebbing, and it is a diagnostic factor for pathologies such as cancer. Recently, the micronuclei, a small nucleus that contains a full chromosome or a fragment thereof, has gained much attention. The NE of micronucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 168 publications
(292 reference statements)
0
26
0
7
Order By: Relevance
“…However, it cannot be excluded that genetic damage occurred at later stages of cancer development. It is known that hot drinks cause esophagitis and dysplasia which represent premalignant lesions 28 , and it is well documented that inflammations are associated with an increase of chromosomal aberrations that lead to formation of MN 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot be excluded that genetic damage occurred at later stages of cancer development. It is known that hot drinks cause esophagitis and dysplasia which represent premalignant lesions 28 , and it is well documented that inflammations are associated with an increase of chromosomal aberrations that lead to formation of MN 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear squeezing [ 46 , 47 ] and extensive forces during migration [ 34 ] can lead to transient NER. Noteworthy, nuclear envelope fragility and NER are also associated to other events [ 27 ] such as viral infection [ 86 , 87 , 88 , 89 ], some neuropathies [ 90 ], aging [ 91 ] or as a consequence of impairment in lamin levels [ 91 , 92 , 93 ] or function as in some type of laminopathy [ 94 ]. Over the past 10 years, the research on NE biology has revealed unexpected consequences of its deregulation and has shown the implication of NER in unexpected diseases such as in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus is compartmentalized from the cytoplasm by the Nuclear Envelope (NE), a lipid bilayer reinforced on its inner side by the nuclear lamina, a sheet-like structure of diverse proteins such as Lamin A and B as well as other components (For a review see [ 27 ]). The nucleus is generally rounded and stiffer than the cytoplasm [ 28 ], and thus can be the rate limiting step to the constriction imposed by cell migration.…”
Section: Mechanical Stress During Metastasismentioning
confidence: 99%
See 2 more Smart Citations